Analisis Faktor Determinan Pertumbuhan Pembiayaan Pada Bank Umum Syariah di Indonesia Periode 2016-2024 - 10010321021, Nuraip; Ifa Hanifia Senjiati; Intan Manggala Wijayanti (Bandung Conference Series: Syariah Banking, 2025)
Abstract. The development of financing at Islamic commercial banks in Indonesia shows instability. Fluctuations in growth in recent years. Financing is influenced by several internal and external factors, such as Third Party Funds (DPK), Capital Adequacy Ratio (CAR), and Non-Performing Loan (NPF). The decline in financing growth in the 2016-2024 period is related to the impact of the COVID-19 pandemic, which slows economic activity and reduces financing demand. This study aims to analyze the influence of Third Party Funds (DPK), Capital Adequacy Ratio (CAR), and Non-Performing Loan (NPF) on financing growth at Islamic commercial banks in Indonesia partially and simultaneously. This study uses a quantitative approach using panel data regression analysis with Eviews 12 as its processing tool. The study uses secondary data from annual reports of Islamic commercial banks obtained from the official websites of Islamic commercial banks, for the period 2016-2024. The results of hypothesis testing show that the Third Party Fund Ratio (TPK) has a positive but insignificant effect on financing growth at Islamic commercial banks. CAR has a significant negative effect on financing growth at Islamic commercial banks. NPF has a significant positive effect on financing growth at Islamic commercial banks. Simultaneously, the DPK, CAR, and NPF ratios have a significant effect on financing growth in Islamic commercial banks, the prob value (F-statistic) (0.000000 < 0.05). The coefficient of determination test (R² test) of the panel data regression model between the independent variables: DPK, CAR, and NPF ratios is able to explain the dependent variable of financing growth by 59.97% and the remaining 40.03% is influenced by other factors not found in this study. Abstrak. Perkembangan pembiayaan pada bank umum syariah di Indonesia menunjukan ketidakstabilan . Fluktuasi pertumbuhan beberapa tahun terakhir. pembiayaan dipengaruhi beberapa faktor internal maupun eksternal. Seperti DPK, CAR, dan NPF. Penurunan pertumbuhan pembiayaan pada periode 2016-2024 terkait dengan dampak pandemi COVID-19 memperlambat aktivitas ekonomi dan mangurangi permintaan pembiayaan. penelitian bertujuan menganalisis DPK, CAR, dan NPF mempengaruhi pertumbuhan pembiayaan pada Bank Umum Syariah di Indonesia secara parsial dan simultan. Penelitian ini menggunakan pendekatan kuantitatif menggunakan analisis regresi data panel dengan Eviews 12 sebagai alat pengolahannya. Penelitian menggunakan jenis data sekunder laporan tahunan bank umum syariah diperoleh dari situs resmi bank umum syariah, selama periode 2016-2024. Hasil pengujian hipotesis membuktikan Rasio DPK berpengaruh positif tidak signifikan terhadap pertumbuhan pembiayaan pada bank umum syariah. CAR berpengaruh negatif signifikan terhadap pertumbuhan pembiayaan pada bank umum syariah. NPF berpengaruh positif signifikan terhadap pertumbuhan pembiayaan bank umum syariah. Secara simultan Rasio DPK, CAR, dan NPF berpengaruh signifikan terhadap pertumbuhan pembiayaan pada bank umum syariah, nilai prob (F-statistik) (0.000000 < 0.05). uji koefisien determinasi (Uji R²) model regresi data panel antara variabel independen: Rasio DPK, CAR, dan NPF mampu menjelaskan variabel dependen pertumbuhan pembiayaan sebesar 59.97% dan sisanya 40.03% dipengaruhi faktor lain yang tidak terdapat pada penelitian ini.